Language and reading comprehension in middle childhood predicts emotional and behaviour difficulties in adolescence for those with permanent childhood hearing loss. (5th September 2017) - Stevenson, Jim; Pimperton, Hannah; Kreppner, Jana; Worsfold, Sarah; Terlektsi, Emmanouela; Mahon, Merle; Kennedy, Colin
Abstract : Background: Permanent childhood hearing loss (PCHL) is associated with an elevated level of emotional and behaviour difficulties (EBD). In children and adolescents with PCHL, EBD has been found to be linked to language ability in children with PCHL. The present study was designed to test whether childhood language and/or reading comprehension abilities of children with PCHL predict subsequent EBD in adolescence. Methods: Language comprehension (LC) and reading comprehension (RC) were measured at ages 6–10 years (Time 1) and 13–20 years (Time 2) in participants with PCHL who preferred to communicate using spoken language ( n  = 57) and a hearing comparison group ( n  = 38). EBD was measured at both time points by parent and by teacher ratings on the Strengths and Difficulties Questionnaire. Results: Within the PCHL group there were negative correlations between EBD scores and concurrent LC and RC scores at Time 1 and at Time 2. Cross‐lagged latent variable models fitted to the longitudinal data indicated that the associations between LC, RC and teacher‐rated EBD were more likely to arise from the impact of LC and RC on behaviour rather than the other way around. Conclusions: In those with PCHL, poor language and reading comprehension in middle childhood increased the risk of emotional and behaviour difficulties at school in the teenage years. The results suggest that effective language and literacy interventions for children with hearing loss may also bring benefits to their mental health.